Effectiveness of asmaul husna dhikr therapy to enhance the self control of alcohol abuser - Fuad Nashori; Ina Noor Khiyar Nafisa; Rumiani Rumiani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Abstract This research was conducted aiming to find out whether Asmaul Husna dhikr could be using a treatment to enhance self-control among alcohol abusers. There were 18 alcohol abusers age between 18 to 40 years old as subject divided into two groups. The research used quasi-experimental method with nonrandomized pretest-posttest-control group design, comparing the conditions before and after treatment between two groups. Self-control was measured by The Brief Self Control Scale (BSCS) adapted from Tangney, Baumister, and Boone (2004) scale, which self-discipline, deliberate, healthy habits, work ethic and reliability as self-control aspects. The experimental group participated in asmaul husna dhikr activities for about 2 weeks. The result showed significant differences in self-control score between experimental group and control group, by its significant level showing p = 0.001 (p < 0.05). Thus, asmaul husna dhikr could be an effective treatment for enhancing self-control among alcohol abusers.